Effects of digital learning intervention on pre-service teachers’ innovation competence: evidence from Kazakhstan - Zhazira Stambekova; Aziya Zhumabayeva; Zhanna Zhussupova; Saule Zhorayeva (International Journal of Evaluation and Research in Education (IJERE), 2026)
Developing innovation competence (IC) is essential for pre-service teachers, as it enables them to effectively design, implement, and adapt instruction in increasingly complex and digitally enriched learning environments where technology integration, student-centered approaches, and pedagogical flexibility are critical. However, empirical evidence on how structured digital learning interventions (DLIs) foster multidimensional IC remains limited. This study examined the effect of a twelve-week structured DLI on IC in 156 third-year pre-service teachers using a quasi-experimental pretest–posttest design with a non-equivalent control group (CG). Participants completed the IC scale before and after the intervention. Results showed that the intervention significantly improved overall IC and all four dimensions: creative problem-solving (CPS), pedagogical adaptability, proactive initiative, and technology-enhanced instructional design, with the largest gains in CPS and technology-enhanced instructional design. Engagement with digital learning activities further predicted competence development, particularly in the intervention group. These findings suggest that integrating structured digital learning with intentional pedagogical design can effectively enhance innovation-oriented competencies. Teacher education programs can apply these insights to design interventions that prepare future educators for innovative, technology-rich classrooms.